The impact of diaper design on mitigating known causes of diaper dermatitis. Issue 6 (30th August 2018) - Gustin, Jennifer; Gibb, Roger; Maltbie, David; Roe, Donald; Waimin Siu, Susana
Abstract: Background: Diapers play a critical role in infant health. In addition to providing sanitary methods of disposing of urine and feces, they can also directly impact skin health. Prolonged exposure to wetness and fecal matter has been shown to be a key driver of diaper dermatitis. This study sought to evaluate how diaper construction can affect absorption of stool. Methods: Methods included laboratory testing of stool absorbency as well as an at‐home diaper evaluation study, which examined a diaper's ability to keep fecal matter from the skin. Breastfed infant stool was given special consideration, as its properties make it difficult to contain. Results: Laboratory results demonstrated that a meshlike aperture diaper was better able to absorb fecal matter. The at‐home diaper evaluation study confirmed that a meshlike aperture diaper design resulted in fewer instances of stool being present on skin during diaper changes. Conclusion: Diapers with a meshlike aperture topsheet may represent a better way to mitigate known causes of diaper dermatitis through their superior ability to absorb fecal matter.